Comparative Analysis of Local Rituals and Folk Beliefs (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper compares folk ritual specialists in Amami and Okinawa, Japan, with those in Uzbekistan. In Amami and Okinawa, noro and yuta perform communal and individual rituals, divination, and healing. In Uzbekistan, spiritually gifted individuals - behalfa, gulgir, murdashuy, domlo, and folbin - fulfill similar roles. The study finds that the processes of gaining spiritual authority closely resemble shamanic initiation, indicating a shared shamanic cultural foundation. Noro are officially appointed ritualists, while yuta are independent shamans. Beharfa correspond to noro, and the other Uzbek specialists collectively correspond to a yuta. Differences in divine status reflect the influence of Islam in Uzbekistan versus traditional beliefs in Amami. This comparative analysis demonstrates how shamanic culture persists and shapes ritual practices and spiritual authority across different regions.